PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN (STUDI PADA KONSUMEN BAKOEL ESKRIM CABANG TEMBALANG) - Iqbal, Muhammad; DS, Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2020)
At present the development of business in the culinary field is growing rapidly, so is the ice cream shop business. One of them is Bakoel Eskrim, although it already has many customers, Bakoel Eskrim's income tends to decrease every year. The purpose of this study is to determine the influence ofÂ  service quality and product quality to the costumer satisfaction in Bakoel Eskrim of Tembalang Branch. The sample size amounted to 97 respondents, where respondents were costumers who was shopping at Bakoel Eskrim, at least 15 years old, and domiciled in the city of Semarang both permanent and temporary. This study consists of 3 variables, 16 indicators and 3 hypothesis. Data analysis technique employed SPSS 26.0 for Windows, to test the validity, reliability test, correlation coefficient test, coefficient of determination test, simple linear regression , multiple linear regression analysis and significance test ( t test and F test). The results showed that partially the service quality positively influenced and significant to the customers satisfaction, which showed by equation Y = 6,131+ 0,653X1.A nd product quality also positively influenced and significant to the customers' satisfaction, which showed by equation Y = 8,346 + 1,175X2. Service quality and product quality also can be seen that simultaneously positive influenced and significant to the customers' satisfaction, which showed by equation Y = 3,973 + 0,314X1 + 0,896X2. Based on these results it is recommended that Bakoel Ice Cream can maintain the quality of service and the quality of products that have received good ratings from consumers and improve ratings that still do not meet costumer expectations such as the hygiene of the eating place and the provision of facilities that supporting convenience of the costumers.